Interspousal contracts: banishing old myths about the prohibition of article 312 of Civil Code - Santillán Santa Cruz, Romina (2020)
The regulation of recruitment between spouses may vary in each legal system depending on the model of management of marital property adopted by the latter. Some comparative Laws, such as Spanish Law, allow for broad freedom of recruitment between spouses, considering that marriage should not limit their freedom to contract. Instead, Peruvian Law prohibits spouses to contract each other with respect of their common property. But this impediment requires a restrictive interpretation for knowing the real scope of article 312 of Civil Code, since the prohibition provided in this rule does not seem to apply to the personal property of each spouse. If so, the so-called agreements of attribution of common nature to personal property, regulated in foreign legal systems, could also be used in Peruvian Law. For these reasons, this work offers a study about the recruitment between spouses in Peru in order to know its strict scope, grounds and purpose of the prohibition mentioned. Similarly, I make a brief analysis of the practical effects that would be presented because of the new interpretation that I would like to propose and which is centred on the concept of “property of society” contained in article 312 of Civil Code.